Gender Perceptions of the Implementation of Rubbish Clean Environment Education in Susupu Village, Sahu District, West Halmahera Regency - Yumima Sinyo; Hernita Pasongli; Syarifuddin Adjam (PT FORMOSA CENDEKIA GLOBAL, 2023)
Gender perceptions regarding environmental education, waste utilization and environmental prevention are efforts made to preserve the environment and prevent pollution and environmental damage caused by waste. The purpose of this research knowing and analyzing gender perceptions in society towards application Environment Education Rubbish Clean in Susupu Village, Sahu District, West Halmahera Regency. This type of quantitative descriptive research uses proportional random sampling based on the number of genders. The results of the research showed that on the environmental education socialization indicator, 8 respondents (10.26%) said it was very good, 57 respondents (73.08%) said it was good, 10 respondents (12.82%) said it was not good and 3 respondents (3.84%) said it was good. %) said it was very bad. Meanwhile, in terms of prevention indicators, 11 gender respondents said it was very good (14.10%) and 52 respondents said it was good (66.67%), 12 gender respondents (15.38%) said it was not good and 3 respondents said environmental prevention was very bad. percentage of 3.06%.